Dampak Visi dan Misi terhadap Kinerja Di Lingkungan Perusahaan Perikanan Napucinta Makassar - Mansyur, Syahrul; Maedina, Rosida (JSSHA ADPERTISI JOURNAL, 2023)
The main objective of this research is to understand and identify the impact of vision and mission on the performance of the Napucinta Makassaar Fisheries Company. This research uses observations in the company environment. And the questionnaire was deliberately made short and concise in order to get a quick response. The structure of the questions is logistical. The limitations of this research are the limited time frame, limited number of questions, and employee attitudes that do not support limiting the sample size. The population in this study were all employees of PT. Napucinta Makassar as many as 50 people. With the saturated sampling technique, the total sample is 50 people. The research results show that vision and mission have a significant influence on organizational performance.